The sum of the terms equidistant from the beginning and end in an A.P.

Question:

The sum of the terms equidistant from the beginning and end in an A.P. is always same and is equal to the sum of ________ and ________ terms.

Solution:

Let a1a2, ............ abe an A.P with common difference d.

Then kth term is ak = a1 + (k – 1)d and kth term from last is the (n – k + 1)th term from beginning

i. e $a_{n-k+1}=a_{1}+(n-k+1-1) d$

$a_{n-k+1}=a_{1}+(n-k) d$

∴ kth term from beginning + kth term from the end is

$a_{1}+(k-1) d+a_{1}+(n-k) d$

$=2 a_{1}+d(k-1+n-k) d$

$=2 a_{1}+(n-1) d$

$=a_{1}+\left(a_{1}+(n-1) d\right)$

$=a_{1}+a_{n}$

∴ Sum of the terms equidistant from the beginning of an A.P and end of A.P is always same and is equal to sum of first term and nth term or last term of the A.P.

 

 

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now